Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1977
DOI: 10.1128/jb.129.2.770-777.1977
|View full text |Cite
|
Sign up to set email alerts
|

Cell density-dependent growth of Myxococcus xanthus on casein

Abstract: When Myxococcus xanthus FB was grown on 0.2% casein it exhibited a phenomenon we call cooperative growth. That is, above 104 cells per ml, both strains that were studied exhibited increasing growth rates as a function of increasing cell numbers. Between 104 and 107 cells per ml, the mean doubling times of strains YS and TNS decreased from 15.2 to 8 h and 26 to 8.5 h, respectively. The extracellular proteinase activity of the two strains was equivalent and directly proportional to cell number. Cooperative growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
103
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(104 citation statements)
references
References 20 publications
1
103
0
Order By: Relevance
“…Larger groups, therefore, may be able to better defend resources from others, as with coyotes 5 , or ants that utilize cooperative transport, carrying large resources to the nest, thus removing them from competition 86, 87 . Alternatively, collective feeding of a resource comprised of many components can permit the consumption of a larger fraction of that resource, such as biofilms that encapsulate a resource and slow the diffusion of nutrients 88, 89 , or humpback whales that use bubble nets to feed on a school of fish 90 .…”
Section: Resultsmentioning
confidence: 99%
“…Larger groups, therefore, may be able to better defend resources from others, as with coyotes 5 , or ants that utilize cooperative transport, carrying large resources to the nest, thus removing them from competition 86, 87 . Alternatively, collective feeding of a resource comprised of many components can permit the consumption of a larger fraction of that resource, such as biofilms that encapsulate a resource and slow the diffusion of nutrients 88, 89 , or humpback whales that use bubble nets to feed on a school of fish 90 .…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, the function and importance of the many potentially secreted proteins in predation are currently unknown. The degradation of polymers is thought to be a cooperative process (Rosenberg et al, 1977). Thus, if casein is the sole carbon source, then M. xanthus cells only show significant growth above a certain cell density and the growth rate increases with increasing cell density.…”
Section: Predation Secreted Proteins and Secondary Metabolitesmentioning
confidence: 99%
“…To determine if high cell density is necessary for predation, Rosenberg et al (1977) showed that growth in liquid culture on the macromolecule casein is dependent on a high cell density of M. xanthus. Yet, when cultured with hydrolyzed casein, no significant difference in growth rate was observed in cultures with either high or low M. xanthus cell density.…”
Section: Cooperative Vs Solitary Predation In M Xanthusmentioning
confidence: 99%
“…Thus, it will be important for future research to establish whether M. xanthus shows cell density-dependent gene expression of degradative enzymes. Alternatively, regulation could occur at the level of the secretory apparatus or, as Rosenberg et al (1977) proposed, exoenzyme production may be constitutive, and the difference in growth rate could be attributed to reaching a critical extracellular threshold of hydrolytic enzymes required. Also important will be to establish how protein secretion in a shaking flask culture relates to secretion on solid surfaces where diffusion is more limited, and how hydrolysis of the casein protein compares with the lysis of prey.…”
Section: Cooperative Vs Solitary Predation In M Xanthusmentioning
confidence: 99%